A Series of Ultra-Efficient Blue Borane Fluorophores - Bould, Jonathan; Lang, Kamil; Kirakci, Kaplan; Cerdán, Luis; Roca-Sanjuán, Daniel; Francés-Monerris, Antonio; Clegg, William; Waddell, Paul G; Fuciman, Marcel; Polívka, Tomáš; Londesborough, Michael G S (Inorganic chemistry, 2020)
We present the first examples of alkylated derivatives of the macropolyhedral boron hydride, anti-B18H22, which is the gain medium in the first borane laser. This new series of ten highly stable and colorless organic-inorganic hybrid clusters are capable of the conversion of UVA irradiation to blue light with fluorescence quantum yields of unity. This study gives a comprehensive description of their synthesis, isolation, and structural characterization together with a delineation of their photophysical properties using a combined theoretical and experimental approach. Treatment of anti-B18H22 1 with RI (where R = Me or Et) in the presence of AlCl3 gives a series of alkylated derivatives, Rx-anti-B18H22-x (where x = 2 to 6), compounds 2-6, in which the 18-vertex octadecaborane cluster architectures are preserved and yet undergo a linear "polyhedral swelling", depending on the number of cluster alkyl substituents. The use of dichloromethane solvent in the synthetic procedure leads to dichlorination of the borane cluster and increased alkylation to give Me11-anti-B18H9Cl2 11, Me12-anti-B18H8Cl2 12, and Me13-anti-B18H7Cl2 13. All new alkyl derivatives are highly stable, extremely efficient (ΦF = 0.76-1.0) blue fluorophores (λems = 423-427 nm) and are soluble in a wide range of organic solvents and also a polystyrene matrix. The Et4-anti-B18H18 derivative 4b crystallizes from pentane solution in two phases with consequent multiabsorption and multiemission photophysical properties. An ultrafast transient UV-vis absorption spectroscopic study of compounds 4a and 4b reveals that an efficient excited-state absorption at the emission wavelength inhibits the laser performance of these otherwise remarkable luminescent molecules. All these new compounds add to the growing portfolio of octadecaborane-based luminescent species, and in an effort to broaden the perspective on their highly emissive photophysical properties, we highlight emerging patterns that successive substitutions have on the molecular size of the 18-vertex borane cluster structure and the distribution of the electron density within.